The September 2017 SEP Event in Context With the Current Solar Cycle: Mars Express ASPERA‐3/IMA and MAVEN/SEP Observations. Issue 15 (11th August 2018) - Ramstad, Robin; Holmström, Mats; Futaana, Yoshifumi; Lee, Christina O.; Rahmati, Ali; Dunn, Patrick; Lillis, Robert J.; Larson, Davin
Abstract: We use Mars Atmosphere and Volatile Evolution/Solar Energetic Particle (MAVEN/SEP) data to estimate the ranges of particle energies that generate background noise in the Analyzer of Space Plasmas and Energetic Atoms‐3/Ion Mass Analyzer (IMA) instrument on Mars Express. The particles that generate IMA background counts are estimated to be electrons with energies >1 MeV and protons >20 MeV. The September 2017 event at Mars resulted in the strongest flux of energetic particles measured by MAVEN/SEP. We correspondingly use the IMA background data to compare this event with the rest of the last solar cycle and back to 2004, finding the event to be the fourth strongest solar energetic particle event detected by Mars Express. Plain Language Summary: The September 2017 event produced the strongest radiation flux measured at Mars by the Mars Atmosphere and Volatile Evolution (MAVEN) mission since late 2014. Such events may not only have effects on the evolution of the atmosphere but also pose a problem for equipment and future human presence. In order to understand how unusual events such as the September 2017 event are at Mars, we use MAVEN data to estimate the sensitivity to radiation of instruments on the older Mars Express (2004‐) spacecraft. We find the September 2017 event to be the fourth strongest radiation event observed by Mars Express. Key Points: IMA background counts provide the longest available record of penetrating energetic particles at Mars, covering more than a solar cycle Comparison with MAVEN/SEP shows IMA to be sensitive to >1 MeV electrons and >20 MeV protons, with good correlation (ρ = 0.85) Distribution of IMA data shows the September 2017 event to be the fourth strongest SEP event observed by Mars Express (2004–2018)